The clinical meaning of the UIP pattern in fibrotic hypersensitivity pneumonitis on cryobiopsy: A multicentre retrospective study - Simone Petrarulo; Claudia Ravaglia; Sissel Kronborg White; Line Bille Madsen; Frederik Lex; Alessandra Dubini; Elisabetta Fabbri; Elisabeth Bendstrup; Paolo Spagnolo; Sara Piciucchi; Venerino Poletti (Pulmonology)
Fibrotic hypersensitivity pneumonitis (f-HP) is an interstitial lung disease in which various antigens in susceptible individuals may play a pathogenetic role. This study evaluates the role of transbronchial lung cryobiopsy (TBLC) and bronchoalveolar lavage (BAL) in identifying a UIP-like pattern and its association with fibrosis progression. We conducted a multicentre retrospective cohort study of patients diagnosed with f-HP who underwent BAL and TBLC between 2011 and 2023. A UIP-like pattern was defined by the presence of (A) patchy fibrosis and fibroblastic foci or (B) honeycombing ± (A). We investigated BAL’s role in predicting UIP-like patterns within a clinical-radiological-serological framework, examining disease progression in these patients using spirometry and mortality data. A total of 195 patients were enrolled, 59 (30%) of whom exhibited a UIP-like pattern. These patients showed greater lung function decline, lower BAL lymphocytosis (14.4% vs. 37.4%, p < 0.001), higher nintedanib prescription (35% vs. 14%, p < 0.001), and higher 10-year mortality (HR 2.8, 95% CI 1.3–5.8, p = 0.004). f-HP patients with a UIP-like pattern exhibit worse clinical outcomes and higher mortality. In cases of low BAL lymphocytosis with a high pre-test clinical suspicion of f-HP, lung biopsy may not be necessary as it increases the likelihood of identifying a UIP-like pattern.